Intraoral pencil core granuloma with retained pencil lead - Mansi Jain; Sanjay Kumar; Nitin Saroch; Tejinder P Singh (Journal of Family Medicine and Primary Care, 2022)
Foreign body impactions can be frequently seen in childhood as children have a habit of putting different objects in the mouth. These impacted foreign bodies if not removed timely, at times can lead to severe reactions leading to granuloma formation. A simple injury, if ignored, can result in severe damage to oral tissue and even loss of the permanent tooth. Therefore, all penetrating injuries should be carefully assessed and treated timely. This study describes a rarest intraoral case of pencil core granuloma with retained graphite lead inside it that led to severe tissue reactions. Pencil core granuloma has been reported extra orally and on limbs. This case report describes the rarest case reported intraorally.